2001
DOI: 10.1016/s1526-9523(01)00093-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Women's Assessment of Midwifery and Medical Care in Québec, Canada

Abstract: In 1990, the province of Québec, Canada, adopted a law that authorized the evaluation of the practice of midwifery through pilot projects before its legalization. A key objective of this evaluation, as defined by the law, was the documentation of women's assessment of maternity care, especially with regard to humanization and continuity of care. Two to 3 months after birth, 933 midwifery clients and 1,000 physicians' clients, matched on several characteristics, responded to a mailed questionnaire (response rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 11 publications
3
18
0
Order By: Relevance
“…Our findings are similar to those of De Koninck et al (2001), in that approximately 88.5% of physicians' clients of in Quebec hospitals indicated that they wished to deliver in the same setting for birthing if they became pregnant again [22]. …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings are similar to those of De Koninck et al (2001), in that approximately 88.5% of physicians' clients of in Quebec hospitals indicated that they wished to deliver in the same setting for birthing if they became pregnant again [22]. …”
Section: Discussionsupporting
confidence: 90%
“…The self-administered questionnaire that we used had been developed in the context of a study that assessed midwifery practice in Quebec, comparing it to the standard obstetrical care provided in the province [22]. The questionnaire was adapted for the needs of the present study and was written in both English and French.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both quantitative and qualitative data were collected to evaluate the pilot. Results suggest that compared to physician services, midwifery clients were more satisfied and empowered by the care they received, midwifery was associated with greater continuity of care, and midwifery care was associated with fewer obstetrical interventions (Blais & Joubert 1999;Collin et al 1999;De Koninck et al 2001;Fraser et al 1999). An important finding stemming from the research was that of cost-effectiveness.…”
Section: History and Contextmentioning
confidence: 99%
“…Quality: B Quantity: B Consistency: B Women cared for by professional midwives report increased satisfaction in the following areas (De Koninck, 2001;Harvey, 2002;Hodnett, 2000;Hundley, 1997;Oakley, 1995;Shields, 1998;Turnbull, 1996): Professional midwifery care reduces costs when compared with physicians working with similar populations for the following reasons (Blanchette, 1995;Carr, 2000;Harvey, 1996;Oakley, 1995;Oakley, 1996;Turnbull, 1996) …”
Section: Qualitymentioning
confidence: 99%